Peningkatan Ekonomi Melalui Pelatihan Tali Kurdi Desa Lekis Rejo Kecamatan Lubuk Raja - Rosmala Dewi; RR. Dimas Veronica Priharti; Ervin Mardalena; Ratih Triyani; Muhammad Girindra (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This community service activity aims to enhance the skills of the residents of Lekis Rejo Village, Lubuk Raja Subdistrict, through macrame craft training. The training was motivated by the community's need for alternative household economic improvement, especially in the post-pandemic period. The implementation method included planning, theoretical and practical training, monitoring, evaluation, and reporting. The results showed increased motivation and skills among participants in creating functional products such as pot hangers and mask connectors. Moreover, the training sparked entrepreneurial interest among the participants. Thus, this macrame training has proven to make a real contribution in fostering entrepreneurship and improving family income at the village level.